Primary care in supplementary health: assessment of costs in the care of older adult patients with heart diseases - Geórgia Silva Marques; Alessandra Maciel Almeida; Isabel Cristina Gomes; Michele Renata Barbosa da Silva; Bruno Almeida Rezende (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to identify whether implementing a supplementary Primary Health Care (PHC) system makes it possible to reduce care costs for older adults with heart diseases. Methods: a retrospective cohort of 223 patients with heart disease aged ≥ 60 years. Data were obtained from medical records and cost databases, assessed for a period of one year before and after PHC implementation. The results were expressed as mean absolute frequencies for number of hospitalizations and as average annual expenses expressed in dollars (US$) in relation to cost data. Results: there was a reduction in hospitalization expenses after implementing supplementary PHC (p=0.01) and a decrease in the frequency of hospitalizations for the entire sample (p=0.006). There was a reduction in the frequency of consultations at the Emergency Room among frail older adults (p=0.011). Conclusions: there was a reduction in hospitalization costs and frequency of visits to the Emergency Room after supplementary PHC.